Dinamika Promosi dalam Era Global - Ahmad Arrasyid, Abduh Malik; Sri Wahyuni, Erika; Suhairi (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
The purpose of this study is to tell or educate readers about the global promotion dynamics. This study employs a quantitative literature review as its type of research. The research method involves combining data from multiple sources, such as books and the internet, into a single one. Finding the necessary information is the method that is used to collect the data. Human thinking and behavior can be altered by rapid technological advancement, particularly in marketing mix strategies like advertising, customer promotion, personal selling, and publicity. The promotion of goods and services has seen a rapid rise in the use of technology and informatics systems like the internet and cyberspace. Manufacturers can use this opportunity to inform, offer, persuade, motivate, and even "force" consumers to try, buy, and even become loyal customers by taking advantage of this technology at very low costs. They can also use it to penetrate borders between countries. This technological advancement benefits consumers as well as producers. Customers are able to quickly obtain product-specific information. As a result, production and consumption systems as well as all aspects of life can benefit from technological advancements